Ischemic heart disease 2 - Lal, Vivek (Henry Stewart Talks, 2015)
Management of IHD: aims and objectives, Non-pharmacological and pharmacological management of IHD, Acute MI: treatment strategies, PCI and stenting, Complications of MI & management, Overall prognosis after MI, Prevention of future attacks